Experimenting with Excellence: Quality Assessment in a Mozambican Oral Bible Translation and Transcription Project - Houston, Tobias J. (The Bible translator, 2025)
Although the traditional concepts of accuracy, naturalness, clarity, and now acceptability are generally seen as keys to a quality translation, they are not the only consideration. That is, a quality Bible translation, whether oral or written, can only be appropriately assessed according to what the translation aims to achieve. This article defines quality in Bible translation alongside the expectations of a “translation covenant,” utilising the loyal Bible translation model and embracing the notion that loyalty to the source text author and the intended audience is pivotal for approaching quality assessment in oral Bible translation. Building on this theoretical foundation, this article introduces a specific oral Bible translation and transcription project in northern Mozambique as an experiment in quality assessment and translation excellence. It explores how the project is integrating quality assessment into the operating workflow and how the project’s procedures attempt to ensure quality in the first place. Specifically, this article discusses quality assessment in relation to the oral translation component and the subsequent written version of the translation. Underlying this entire discussion is the commitment to loyalty to both the source text author and the intended audience as an essential component of what constitutes a high-quality oral Bible translation.